Letter: new thresholds need to be defined when using point of care assays to monitor infliximab trough levels in IBD patients. Issue 11 (17th May 2018) - Dutzer, D.; Nasser, Y.; Berger, A. E.; Roblin, X.; Paul, S.
Abstract : Linked Content This article is linked to Papamichael et al paper. To view this article visithttps://doi.org/10.1111/apt.14458 .